Unveiling sex-disparities and the impact of gender-affirming hormone therapy on periodontal health - Villar, Cristina Cunha; Sloniak, Mariane Cristina; Assis, Josiane Betim de; Porto, Renata Cassiano; Romito, Giuseppe Alexandre (Frontiers in Dental Medicine, 2024)
As personalized medicine advances, the need to explore periodontal health across different sexes and gender identities becomes crucial. This narrative review addresses the gap in understanding how biological sex and gender-affirming hormone therapy (GAHT) influence periodontitis risk. Results: Research has uncovered significant sex-based immunological disparities driven by X and Y chromosome gene expression and sex-hormones, which may influence susceptibility to periodontitis. Additionally, preliminary findings suggest that GAHT, particularly testosterone therapy in transgender men, could exacerbate pro-inflammatory cytokine production and alter immune cell responses, which may exacerbate inflammatory pathways crucial in the progression of periodontitis. Conversely, the effects of estrogen therapy in transgender women, although less extensively studied, suggest modifications in B cell functionality. These observations highlight the complex role of GAHT in modulating immune responses that are central to the development and exacerbation of periodontal disease. Discussion: The review highlights a complex interaction between sex hormones, gene expression patterns, immune responses, and periodontitis risk. While cisgender males show increased susceptibility to periodontitis that could be linked to specific immune pathways, GAHT appears to modify these pathways in transgender individuals, potentially altering their risk and disease progression patterns. Conclusion: There is a critical need for more focused research on the direct impacts of GAHT on periodontal health. Understanding the nuances of immune modulation by GAHT will aid in crafting personalized periodontal care for transgender individuals, aligning with the broader goals of inclusive and effective healthcare.